Advancing deep brain stimulation for obsessive––compulsive disorder. (March 2011) - Burdick, Adam P; Foote, Kelly D
Evaluation of: Denys D, Mantione M, Figee M et al. Deep brain stimulation of the nucleus accumbens for treatment-refractory obsessive––compulsive disorder. Arch. Gen. Psychiatry 67(10), 1061––1068 (2010). Herein we review a prospective trial of deep brain stimulation (DBS) for the treatment of severely debilitating, medication-refractory obsessive––compulsive disorder (OCD) recently published in Archives of General Psychiatry by Denys et al. This prospective 16-subject study, while having some technical limitations, is an excellent addition to the existing literature supporting the use of DBS in the region of the nucleus accumbens for severe OCD. It provides further evidence of efficacy and safety, sham versus active stimulation evidence that this efficacy is real, and several key observations on how DBS interacts with the brain that can shed light on the neuropathophysiology of OCD itself.